Analisis Risiko Kandungan Timah Hitam (Pb) pada Ikan Belanak di Sungai Tapak Kota Semarang - Pradipta Dhimasrasta Santya Putra; Sulistiyani Sulistyani; Budiyono Budiyono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Tapak River is a river located in the industrial area Tugurejo suspected of contaminated heavy metals plumbum. Plumbum is a heavy metal that can accumulate in the bodies of animals and is toxic in the human body. The purpose of this study was to analyzed the risk of exposure to plumbuml (Pb) contained in Mugil cephalus consumed by the people in tapak river, Semarang. This study is observational method Environmental Health Risk Analysis (EHRA). Population of the research is 43 men were consuming Mugil cephalus from the tapak river Mugil cephalus and domiciled area of Tugurejo. Results obtained the concentration plumbum in the river is 0.03 mg / L and the concentration of plumbum in the Mugil Cephalus was 0.189 mg / kg for meat and 0.663 mg / kg for fish gills. The results showed the average intake of 0.0004 mg / kg / day for real time, 0.0008 mg / kg / day for a life time of 30 years and 0.0013 for a life time of 50 yearswith an average rate of intake was 400 g / day with an average frequency of 144 days / year and the average duration of exposure of 11 years.The conclusion is the Mugil cephalus in the tapak river safely consumed in real time conditions and a life time of 30 years (RQ <1), whereas mullets unsafe for consumption on the conditions of life time of 50 years (RQ ≥ 1).